2021
DOI: 10.3390/cells10081857
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Distinct Distributions of Dendritic Cells in Autoimmune Dry Eye Murine Model

Abstract: We investigated whether aging-dependent changes in dendritic cell (DC) distributions are distinct in autoimmune dry eye compared with an aging-related murine model. Corneal staining and tear secretion were evaluated in young and aged C57BL/6 (B6) and NOD.B10.H2b mice (NOD). In the corneolimbus, lacrimal gland (LG), and mesenteric lymph node (MLN), CD11b− and CD11b+ DCs, CD103+ DCs and MHC-IIhi B cells were compared between young and aged B6 and NOD mice. With increased corneal staining, tear secretion decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Aging can also affect immune cell phenotypes and their distribution at the ocular surface (Golebiowski et al, 2020;McClellan et al, 2014). In mice, a higher proportion of CD11b + CD11c + DCs was observed in aged mouse corneas compared to in younger eyes (Jung et al, 2021). Among the DC subtypes, CD11b-CD11c+ DCs induce cytotoxic CD8 + T cell and Th1 responses, while CD11b + CD11c + DCs initial Th17 and Treg responses (Sun et al, 2020).…”
Section: Role Of Aging In Corneal Neuroimmune Interactionsmentioning
confidence: 99%
“…Aging can also affect immune cell phenotypes and their distribution at the ocular surface (Golebiowski et al, 2020;McClellan et al, 2014). In mice, a higher proportion of CD11b + CD11c + DCs was observed in aged mouse corneas compared to in younger eyes (Jung et al, 2021). Among the DC subtypes, CD11b-CD11c+ DCs induce cytotoxic CD8 + T cell and Th1 responses, while CD11b + CD11c + DCs initial Th17 and Treg responses (Sun et al, 2020).…”
Section: Role Of Aging In Corneal Neuroimmune Interactionsmentioning
confidence: 99%
“…Antigens that bypass the THO-injured epithelial barrier are captured by skillful antigen-presenting DCs that reside in the corneal epithelium. THO induces an increased activation and maturation of DCs and promotes their recruitment in inflamed corneas and conjunctivas by enhancing the expression of adhesion molecules on epithelial and endothelial cells [50,51]. Accordingly, one study observed a significantly increased number of activated DCs in the ocular surfaces of THO mice compared to healthy controls (Figure 3) [51].…”
Section: Tho-dependent Activation Of T Cell-driven Detrimental Immune...mentioning
confidence: 99%
“…THO induces an increased activation and maturation of DCs and promotes their recruitment in inflamed corneas and conjunctivas by enhancing the expression of adhesion molecules on epithelial and endothelial cells [50,51]. Accordingly, one study observed a significantly increased number of activated DCs in the ocular surfaces of THO mice compared to healthy controls (Figure 3) [51]. Upon the engulfment of invading pathogens, activated DCs process their antigens and present them to naïve CD4+ T lymphocytes in regional lymph nodes.…”
Section: Tho-dependent Activation Of T Cell-driven Detrimental Immune...mentioning
confidence: 99%
“…DCs, a diverse group of immune cells, play a critical role in antigen presentation and immune response regulation. These cells are present in various tissues, including lacrimal glands [11,133]. In our studies of mouse lacrimal glands, we first discovered the presence of predendritic cells (pre-DCs), which are the precursors of DCs.…”
Section: Dc/pdcs In Mouse Lacrimal Glandsmentioning
confidence: 99%